THE EFFECT OF INTRAPERSONAL DIFFERENCES AMONG DIFFERENT FACTORS OF METACOGNITIVE AWARENESS OF L2 LISTENING ON THE UNDERGRADUATE EFL BANGLADESHI LEARNERS - Azran Azmee Kafia (Indonesian EFL Journal, 2021)
Drawing on Flavell’s (1979) conception of metacognition, Vandergrift and Goh (2012) proposed a metacognitive framework for L2 listening to facilitate listening comprehension and help learners cope with listening difficulties by influencing their operations through processes of planning, monitoring, problem-solving, and evaluation. This study was executed to find if there is any intrapersonal difference among five factors of metacognitive awareness of L2 listening, and which factors are the most used by the high achievers and low achievers for their successful listening comprehension. The overall purpose of the study was to investigate i) what factors did play the role among high achievers and low achievers, and ii) what are the interpersonal differences among the factors; planning and evaluation, person knowledge, problem-solving, directed attention and mental translation, for L2 listening comprehension. To apprehend the research objectives, twelve Bangladeshi undergraduate EFL learners in the experimental group (06) and control group (06) received metacognitive instruction and traditional instruction based on product approach respectively for 5 weeks using five transactional listening texts. To gauge the changes, a pre-test, a post-test and two metacognitive awareness listening questionnaires (MALQ) were administrated. The quantitative method research embodied the notion of triangulation for this study. Using a one-way within-subjects ANOVA, the result revealed that there was a significant effect of metacognitive awareness factors on L2 listening comprehension accounted for over 65% of the total variance in the data.Keyword: metacognitive instruction; MALQ; metacognitive awareness